(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The aim of the research is to reveal the effect of Facebook on the personality of the classroom teacher students in the faculty of education at Tishreen University in light of the corona pandemic. Use the descriptive method. the sample included (256) classroom teacher students in the faculty of education at Tishreen University for the academic year 2021- 2022. To achieve the goal of the research a questionnaire was designed that consisted of (26) phrases distributed over three axes, it is sides (the cognitive, the emotional, the behavioral) of the students’ personality. The results of the research showed the degree of influence of Facebook on the personality of the classroom teacher students in the faculty of education at Tishreen University in the light of the corona pandemic came average, and a statistically significant difference was found between the average grades of the sample according to the variable of the place of residence in favor the students residing in the city, and according to the variable of the school year in favor of the first and second academic year. The research made several recommendations, the most important of which was: the necessity of placing a special focus on media education in the educational media syllabus, to educate students about the effects of social media on their personality and conducting other research on the positive and negative effects of social media on students.